PENGARUH GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN DI BEI TAHUN 2019-2023 - Ikbal Ikbal; Bustang Bustang; Surianto Ilham (Jurnal Akuntansi Kompetif, 2026)
This study uses a quantitative approach with secondary data obtained from financial statements, annual reports, and company sustainability reports. The research sample was determined using a purposive sampling method and resulted in 8 mining companies with a total of 40 observation data over five years. The independent variable in this study is Green Accounting, measured using a dummy variable based on the disclosure of environmental costs in the sustainability report, while the dependent variable is financial performance measured using Return on Assets (ROA). Data analysis was conducted using descriptive statistical analysis, classical assumption tests, and simple linear regression analysis with the help of SPSS software. The results show that the implementation of Green Accounting has no effect on the financial performance of mining companies. This indicates that environmental costs incurred by companies are more considered as a burden that can reduce profits in the short term, so they do not have a direct financial impact on the company. These findings indicate that the implementation of Green Accounting in mining companies is still not a determining factor in improving the company's financial performance